Islam and H. G. Nahuys’ Memoirs on the Java War 1825-1830 - Syahid, Achmad (Studia Islamika, 2020)
This article analyzes the worldview of the memoir of H.G. Nahuys van Burgst, Resident of Surakarta, entitled Verzameling van officiele Rapporten, betreffende den Oorlog op Java in de Jarren 1825-1830, as a polemic with H.J.J.L. Ridder de Stuer. His memoirs represent a typical Dutch government worldview based more on colonial interests and power tendencies. The colonial interests made colonial goverment have a tendency and take a certain position from the start against Islam and the cultural and Islamic characterist resistance movements launched by Diponegoro and Kiai Modjo. The descriptive analysis of the memoirs about the Javanese War which is presented chronologically makes it easy for us to reveal how war figures put Islam as the motivation for war, the spirit, the basis for thinking, the strengthening of the support network, the basis for regulation, and the justification for starting or ending the war. Meanwhile, the colonial government saw Islam as being used as a foster for the character’s socio-vertical mobility ambitions, as an identity, propaganda material, and procedures in oath-taking ceremonies.